Nilai Pendidikan Islam dalam Perspektif Ekologi Lingkungan di Bumi Langit Imogiri Yogyakarta - Syafitri, Lely Nur Hidayah (Jurnal Pendidikan Dewantara, 2023)
Humans are endowed with intelligence that can exploit and utilise the natural environment to improve their welfare and survival. However, human greed can cause damage or use natural resources beyond their capacity. So humans need to preserve their environment. These efforts have been reflected by Bumi Langit Institute as a solution to technological advances. This research uses a qualitative research approach, which involves research in the field and uses data collection methods such as observation, interviews, and recording. The results show that humans and nature are interconnected, as both contribute to maintaining environmental balance. The Islamic Education values of Bumi Langit Institute are simplicity, gratitude to Allah, awareness value, being kind to Allah, preserving each other, devotion value, giving selflessly, sincerity.